067 Injury prevention: exploring factors affecting adherence to different exercise programmes in men's community rugby union. (3rd March 2020) - Attwood, Matthew; McKay, Carly; Roberts, Simon; Trewartha, Grant; Stokes, Keith
Abstract : Background: Performing injury-prevention exercise programmes can reduce sport injury risk, but their effect is influenced by programme adherence. Barriers and facilitators to injury-prevention programmes in a range of sports are recognised, but whether the same factors influence implementation in rugby union is unknown. Objective: To determine facilitators and barriers to implementation (adherence) of 'Activate', an injury prevention exercise programme in men's community rugby union. Design: Qualitative study alongside a randomised controlled trial. Setting: Community rugby clubs in English leagues 4–7 (semi-professional to recreational level). Participants: Sixteen clubs were randomised (single-blind: Activate=8/'active' control=8), from which fourteen staff (Activate staff=10: 'active' control staff=4) who delivered the exercise programmes ('delivery agents': head coach=8; player coach=3; assistant coach=2; player delivering warm-up=1) were interviewed. Interventions: A rugby-specific injury-prevention exercise programme. Main outcome measurements: Semi-structured interviews were conducted mid-season, exploring facilitators and barriers to exercise programme implementation. Results: Training for delivery-agents, availability of programme tools/materials, self-efficacy of delivery-agents, player-welfare and good peer understanding were the most common facilitators in both intervention and control clubs. Perceived benefits, team organisation and programme duration were the least common responses. The most common barriers were: ground-based exercises, bad weather (rain/cold) and perception of programme duration, in both intervention and control clubs. The inclusion of static exercises were commonly identified as a barrier to the intervention programme only. Conclusions: Factors influencing the translation of injury-prevention research into practice within men's community rugby are consistent with previous research. Ground-based, slow-paced exercises to be performed in poor weather conditions should be minimised as they reduce programme adherence. The nature of some movement-control (intervention) exercises, where players focussed on limb-alignment rather than game-play (touch-rugby), were perceived as protracting warm-up duration and were barriers. Programme tools (laminated cards) facilitate programme use, while programmes need to replicate game-play conditions so players feel sufficiently prepared for what is an intense contact sport.